Specificity of Performance Interpretation of Hennady Liashenko`s Quartet №1 - Feshchak, Nataliia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
The relevance of the investigation. For the first time in Ukrainian music studies, the partiture of a famous Ukrainian composer H. Liashenko is studied. In the case of the partiture, the peculiarities of interpretation of linguistic, figurative system, specifics of musical form are investigated. In the article, it is stated, that the main stylistics method of the quartet is a neo-folkloric performance tendency. The genre and stylistic features of the work have been studied by the method of integral musical and theoretical analysis, the figurative content of the quartet has been determined, the features of the formation and use of compositional means of expressiveness (intonational structure of the main elements of the form, methods of development of the thematic material) have been revealed. Complex interpretation analysis is used in studying the peculiarities of the use of quartet performing expressive means (articulation, strokes, vibration) in their interaction with compositional means. Various forms of vibrato in the quartet score have been studied, which deepens the notion of the characteristic of the timbre of string-bow instruments and contributes to the life-like colorful sound of the quartet ensemble. Conclusions. Different expedients of cantilena sound in Quartet №1, borrowings of folk performance manner coexist with specific and detailed timbral and dashed differentiation of quartet performance. Amid them there is vibrato technique as well, as it is an important mean of musical expression of a quartet performer. The practical implications of results of the given work are in the field of usage in the real quartet class, as well as in educative classes or workshops concerning with quartet methodology and performance history of bow instruments.